From Research Influencers to Substance Use Policymakers: Bibliometrics Demonstrate Translation From Research to Policy. - Llewellyn, Nicole M.; Weber, Amber; Kegley, Supriya; Nehl, Eric J.; Abraham, Amanda J. (Journal of Studies on Alcohol & Drugs, 2026)
Objective: The public health impact of substance use is substantial, with tobacco use and excessive drinking leading as causes of death in the United States. To address this growing epidemic, governments have implemented a range of substance use-related policies. The National Institutes of Health's Clinical and Translational Science Awards (CTSA) program, which aims to accelerate the translation of research findings into health impact, may advance translation by shaping the policy literature that informs policymakers, health professionals, and the public. Using innovative bibliometric tools, this study evaluates how CTSA-supported research published from 2006 to 2023 has influenced substance use-related policy literature. Method: The authors identified 135,000 publications that acknowledged CTSA support. Those publications were queried in the Overton Policy Database, which indexes references to research publications in global policy literature. Results: Thus far, CTSA-supported publications have been cited in 3,451 policy documents identified as substance use-related according to Overton's Topics field. Substance use-related Topics were classified into the top categories of Tobacco, Opioids, Cannabis, Alcohol, and General/Other substance use. Policy documents came from 321 organizations across 49 countries--often governments, health agencies, or political think tanks, including the World Health Organization, Guidelines in PubMed Central, and the RAND Corporation. The authors present case illustrations of individual research publications that have had a notable influence on substance use policy. Conclusions: By elucidating how supported publications are applied beyond academia, bibliometrics offer a useful avenue for evaluating the translational impact of programs in specific policy areas. Our findings showcase the impact of CTSA research on the substance use-related policy literature, an important area of health policy.